Gender differences among persons entering medication treatment for opioid use disorder in the community. Issue 5 (2nd June 2022) - Di Paola, Angela; Taweh, Noor; Biondi, Breanne E.; Forray, Ariadna; Frank, Cynthia A.; Shaw, Albert; Springer, Sandra A.
Abstract: Background and Objectives: We evaluated gender differences among persons initiating medications for opioid use disorder (MOUD). Methods: Analyses of baseline assessments for a study evaluating the impact of MOUD on outcomes included: demographics, DSM‐5 diagnoses, depression severity, quality of life (QoL), and medication history ( N = 125). Results: When compared to men, women had a greater prevalence of generalized anxiety and posttraumatic stress disorders; and worse psychological QoL. Women were less likely to be prescribed psychiatric medications. Discussion and Conclusions: Women may benefit from tailored multidisciplinary programs with MOUD. Scientific Significance: This study identified that women with OUD seeking MOUD in the community had greater sedative hypnotic nonprescribed medication use and psychiatric comorbidity than men, all of which can contribute to poorer retention on MOUD and higher risk of morbidity and mortality. Thus, concurrent psychiatric disorder screening and treatment integrated with MOUD may improve retention on MOUD, opioid relapse and overdose for women.